Bauhaus journal 1926-1931 : facsimile edition - Müller, Lars, 1955- (Lars Müller Publishers ; Bauhaus-Archiv/Museum für Gestaltung, 2019)
One hundred years after the founding of Bauhaus, it's time to revisit Bauhaus journal as a significant written testimony of this iconic movement of modern art. In this journal, published periodically from 1926 to 1931, the most important voices of the movement are heard: masters of the Bauhaus, among others, Josef Albers, Walter Gropius, Wassily Kandinsky, Paul Klee, László Moholy-Nagy, and Oskar Schlemmer, as well as Herbert Bayer, Marcel Breuer, Ludwig Mies van der Rohe, Gerrit Rietveld and many more. They address the developments in and around the Bauhaus, the methods and focal points of their own teaching, and current projects of students and masters. At the time primarily addressed to the members of the"circle of friends of the Bauhaus," the journal published by Gropius and Moholy-Nagy makes tangible the authentic voice of this mouthpiece of the avant-garde. The facsimile reprint is intended to give new impetus to international discussion and research on the Bauhaus, its theories and designs.
Published in collaboration with Bauhaus-Archiv/Museum für Gestaltung, Berlin
Commentary and english translation
Keywords: Bauhaus; moderní architektura -- 20. století; moderní umění -- 20. století; design -- 20. století; časopisy; modern architecture -- 20th century; modern art -- 20th century; design -- 20th century; journals; komentáře; commentaries